Seimbangkan Langkahmu dengan Ankle Theraband dan Lateral Hop di RW 07 Kelurahan Tomang Jakarta Barat - Astrid Komala Dewi; Yurita Mailintina; Catherine Hermawan Salim (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
In most cases, "motion" means changing the location of part or all of a living being's body. Since there is no life on Earth without movement, humans, like all living creatures, must move. The ability to balance is influenced by a number of systems, including the nervous system, musculoskeletal system, and sensory system. People in RW 07, Tomang Village, West Jakarta, hope to improve their balance and body strength through the use of Ankle Theraband and Lateral Hop exercises. There were 30 respondents involved in this activity. After the task was completed, the success measurement method was used to listen to the pre and post-test methods, and an N-Gain score of 0.7 indicated that the strength or category in this study was at a moderate level. The calculation results show an increase of 50% from the pre-test and post-test results. This shows that respondents experienced positive changes after participating in the activities and that the techniques they used could improve their learning outcomes.